MicroRNA-21 as a biomarker for ovarian cancer detection - Aprilia Indra Kartika; Siti Nur Chasanah; Akbar Satria Fitriawan; Dewi Sahfitri Tanjung; Addin Trirahmanto; Heru Pradjatmo; Teguh Aryandono; Sofia Mubarika Haryana (Universitas Gadjah Mada, 2018)
Ovarian cancer is a lethal disease. One of the problems faced by patients with ovarian cancer is the lack of symptoms in its early stages, which results in it only being detected when it is at an advanced stage. Therefore, there is an urgent need for biomarkers that can predict ovarian cancer precisely. The purpose of this study was to determine the expression of microRNA-21 as a predictive biomarker candidate in both early- and advanced-stage ovarian cancer. This was a cross-sectional study using the blood plasma of 21 healthy control subjects and 37 blood plasma samples from patients with ovarian cancer. Blood plasmas were collected, from which the RNA was isolated. Based on the RNA, the cDNA was synthesized and run through qPCR, the results of which were analyzed using the Livak method. The results showed an upregulation of microRNA-21 in the advanced stage by 2.14 fold compared with the early stage, and 6.13 fold compared with the healthy controls (p < 0.05). The upregulation of microRNA-21 in early-stage ovarian cancer was 2.86 fold compared with the healthy control subjects (p < 0.05). In addition, there was an increase in the expression of microRNA-21 in ovarian cancer by 4.14 fold compared with the healthy controls (p < 0.05). Based on these results, it can be concluded that the expression of microRNA 21 upregulated with the severity of the disease.